Dead Tumor Cells Expressing Infectious Salmon Anemia Virus Fusogenic Protein Favor Antigen Cross-Priming In Vitro - Morales, Jonathan; Barrera-Avalos, Carlos; Castro, Carlos; Castillo, Stephanie; Barrientos, Claudio; Robles-Planells, Claudia; López, Ximena; Torres, Ernesto; Montoya, Margarita; Cortez-San Martín, Marcelo; Riquelme, Denise; Escobar, Alejandro; et al. (Frontiers in Immunology, 2017)
Antigen cross-presentation is a crucial step in the assembly of an antitumor immune response leading to activation of naïve CD8 T cells. This process has been extensively used in clinical trials, in which dendritic cells generated in vitro are loaded with tumor antigens and then auto transplanted to the patients. Recently, the use of autologous transplant of dendritic cells fused with dying tumor cells has demonstrated good results in clinical studies. In this work, we generated a similar process in vivo by treating mice with dead tumor cells (cell bodies) expressing the fusogenic protein of the Infectious salmon anemia virus (ISAV). ISAV fusion protein retains its fusogenic capability when is expressed on mammalian cells in vitro and the cell bodies expressing it facilitates DCs maturation, antigen transfer by APCs, and increase cross-presentation by DCs in vitro. Additionally, we observed in the melanoma model that cell bodies with or without ISAV fusion protein, reduce tumor growth in prophylactic treatment however, only ISAV expressing cell bodies showed an increase CD4 and CD8 cells in spleen. Overall, our results suggest cell bodies could be used as a complement with other type of strategies to amplify anti-tumor immune response.